Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Kelas X MAN Kaur - Andrian Solihin (Yayasan Darusssalam Bengkulu, 2025)
The aim of this research is to determine the influence of the Problem Based Learning Model on the Learning Outcomes of Class X Man Kaur Students. This type of research is quantitative with a quasi-experimental approach. The sampling technique uses simple random sampling and data collection techniques through tests (Pretest and Posttest). Data analysis for both groups used the t-test (Independent Samples Test) with the help of the SPSS Version 26.0 program. The results of data analysis show that class amounting to 81.78 with the lowest score of 60, the highest score of 100. From the results of the independent sample t test calculation which compares the posttest and pretest scores at a significance level of 0.05, a sig. (2-tailed) of 0,000 (Ha) significance value < 0.05. So it can be concluded that there is an influence of the Problem Based Learning Model on the Learning Outcomes of Class X Man Kaur Students